2009
DOI: 10.1093/fampra/cmp005
|View full text |Cite
|
Sign up to set email alerts
|

Do family physicians' records fit guideline diagnosed COPD?

Abstract: There is still considerable underpresentation and underdiagnosis of COPD in family practice. As FPs focus on presented symptoms and as detection increases with the frequency of practice visits, diagnostic guidelines should stress the importance of persistent cough and phlegm to support timely diagnosis of COPD in family practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 29 publications
(27 reference statements)
1
32
0
Order By: Relevance
“…In effect, underdiagnosis has been shown in earlier epidemiological studies of COPD among primary care patients [9,11,31]. These studies have shown that underdiagnosis of COPD occured partly because of "doctor's delay", i.e., doctors who don't suspect underlying COPD [32,33] and partly because of "patient's delay", i.e, patients who self-report good health [34]. …”
Section: Discussionmentioning
confidence: 99%
“…In effect, underdiagnosis has been shown in earlier epidemiological studies of COPD among primary care patients [9,11,31]. These studies have shown that underdiagnosis of COPD occured partly because of "doctor's delay", i.e., doctors who don't suspect underlying COPD [32,33] and partly because of "patient's delay", i.e, patients who self-report good health [34]. …”
Section: Discussionmentioning
confidence: 99%
“…3 Physicians often have a low index of suspicion of COPD, especially in women and midlife patients. [4][5][6] Heterogeneity in clinical presentation of COPD compounds the challenge for primary care; COPD comprises multiple phenotypes, affecting the disease pathology (eg, chronic bronchitis, Primary Care Strategies for COPD emphysema, or airways disease) and its natural history (frequent exacerbations, pulmonary cachexia, exercise intolerance, or hyperresponsive airways). 7 Among patients referred to pulmonary practices, the time lag between initial primary care presentation and definitive COPD diagnosis averages 7 to 15 years-a period of increasing symptoms, declining activity, risk of exacerbations, and perceptibly worsening health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…7 Among patients referred to pulmonary practices, the time lag between initial primary care presentation and definitive COPD diagnosis averages 7 to 15 years-a period of increasing symptoms, declining activity, risk of exacerbations, and perceptibly worsening health-related quality of life. 4,6 Once recognized, COPD may still be inadequately treated due to health care providers' therapeutic pessimism. 5 When COPD treatment is undertaken, it often falls prey to systemic preoccupation with acute care.…”
Section: Introductionmentioning
confidence: 99%
“…All these documents give recommendations on how to improve the diagnosis and treatment of COPD patients and to control the costs of this disease. However, there are many proofs that guideline recommendations for management of COPD are not adequately followed in clinical practice both by GPs [27] and also by some respiratory specialists especially in relation to treatment [28,29]. In particular, the observed prevalence of COPD in records of GPs is notably lower than would be expected according to what found using health questionnaires and specific studies [30] and this means that a great part of patients are not diagnosed and consequently not treated.…”
Section: Introductionmentioning
confidence: 99%